Unveiling the Nexus: Critical Thinking and Academic Achievement in Grade XI at SMAN 3 Palopo - Erika Immanuela Silas; Ismail Ismail; A.Irma Suryani (Biology and Biology Education Journal, 2024)
The development of information and communication technology demands that learners enhance their critical thinking skills to filter accurate information, thereby achieving truth and a proper understanding of the knowledge around them. This is also expected to help improve students' learning outcomes. The research used in this study is quantitative descriptive research with the aim of determining the relationship between critical thinking skills and student learning outcomes in biology, specifically in the digestive system topic for Grade XI. The research subjects used were all Grade XI science students at SMAN 3 Palopo. The determination of the subjects used the Slovin formula, resulting in a sample size of 147 students. The sampling technique employed was purposive sampling. Data collection in the research utilized two instruments: a critical thinking skills test consisting of 10 essay questions adjusted to the critical thinking skill indicators according to Ennis and a learning outcomes test consisting of 20 multiple-choice questions adjusted to the cognitive dimension indicators of Bloom's revised taxonomy according to Anderson & Krathwohl. Data on critical thinking skills and student learning outcomes were analyzed descriptively, and prerequisite tests were conducted using the Kolmogorov-Smirnov normality test and simple linearity tests. The relationship between critical thinking skills and student learning outcomes was tested using the product-moment correlation test, and the results obtained indicate a very strong and positive relationship between critical thinking skills and learning outcomes. This research is expected to provide insight to educators in their efforts to enhance students' critical thinking skills.